Correlação de indicadores antropométricos e de desempenho muscular em atletas masculino de judô e taekwondo - CRUZ, Amanda Suélen Costa da (2022)
Anthropometric indicators may be associated with performance between Judô and Taekwondo practitioners. The aim of this study was to compare scapular strength and thoraco-lumbar flexibility between Judô and Taekwondô athletes. The study sample consisted of 18 male athletes (11 judô athletes and 7 taekwondo athletes), aged between 18 and 50 years, intentionally selected. As inclusion criteria, they should be as at least black belt in their martial art, with at least five years of practice, usual training regime and competitive experience varying from regional to national. All subjects were submitted to body mass, height, BMI, combined with motor tests of thoraco-lumbar flexibility and scapular strength. The results of the study showed that there were no statistical differences between TKD and JD groups (p<0,05). However, bivariate correlation analysis (Pearson) identified a positive correlation (p <0.05) between body mass and BMI parameters (r = 0.910, p <0.000); body mass and scapular strength (r = 0.581, p <0.015) and between BMI and scapular strength (r = 0.686, p <0.003). There was also a negative correlation between scapular strength and flexibility (r = -0.531, p <0.025). (Figure 2). These results suggest that although the two modalities present different functional characteristics, the athletes of the sample probably present a very similar neuromuscular adaptation, suggesting that this fact may be due to the training that the athletes were submitted.